Effect of different waterlogging periods on biochemistry, growth, and chlorophyll a fluorescence of Arachis hypogaea L. - Sharma, Shubhangani; Bhatt, Upma; Sharma, Jyotshana; Darkalt, Ahmad; Mojski, Jacek; Soni, Vineet (Frontiers in Plant Science, 2022)
Peanut is among the main oil crop in India with huge economic importance. The unpredictable rainy season at growing time of peanut, causes waterlogging in peanut fields. The condition of soil waterlogging is major environmental limitations that negatively affect the growth, physiology and development of peanuts. Thus, the export and production of peanuts are severely affected by waterlogging. Therefore, the understanding of metabolic mechanisms under waterlogging is important to future waterlogging tolerance breeding in peanuts. This study aimed to evaluate how peanuts responded to various waterlogging conditions in terms of their development, metabolic processes, and chlorophyll fluorescence characteristics. The evaluations were carried out on different stage of peanut variety DH-86. The peanut plants were subjected to different waterlogging periods: 20, 40, 60, 80 and 100 days. The growth parameters including, total dry mass, total leaf area, and total leaves number were calculated in all treatments. The phenomenological and specific energy fluxes and maximum photosystem II efficiency (FV/Fm) were also determined. The measurements were done statistically by using PCA, G- mean clustering and correlation analysis to know the interaction between different physiological parameters. The waterlogging for 100 days caused significant reduction in total number of leaves, dry mass and total leaf area. The most sensitive parameters are specific and phenomenological energy fluxes and Fv/Fm, which notably decreased as waterlogging duration increased. The results indicated the growth and physiological performance of the peanut cv. DH-86 were affected significantly due to waterlogging and the interaction between all these parameters in waterlogging. This research focus on how peanuts respond to waterlogging stress and provides the basis for future plant breeding efforts to improving peanut waterlogging tolerance, especially in rainy regions. This will improve the sustainability of the entire peanut industry.